Did investment opportunity moderate the influence of the COVID-19 crisis on dividend policy? - Powell Gian Hartono; Georgina Maria Tinungki; Yuyun Karystin Meilisa Suade; Liana Rahardja; Novika Ayu Triany; Isthi Wahyuning Tyas; Patrick Gunawan Hartono (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
During the COVID-19 crisis, the investment opportunity experienced a low condition, indicated by a decrease in the market price to book value during the crisis, believed to moderate the impact of the COVID-19 crisis on dividend policy, specifically focusing on companies within the real estate and property sector in Indonesia. Therefore, this study examines the effect of the COVID-19 crisis, measured by GDP growth, on dividend policy moderated by investment opportunity. Employing a quantitative approach, the research spans from 2014 to 2021, using a purposive sampling technique to select 31 real estate and property sector companies as samples. Statistical analysis is conducted using dynamic panel data regression, employing the System-Generalized Method of Moments with a Two-Step estimator to produce more efficient parameter estimates and accommodate the dynamics of dividend policy. The findings reveal that during the COVID-19 crisis, companies in this sector tended to adopt higher dividend policies than non-crisis periods. Furthermore, investment opportunity was proven to positively moderate the influence of the COVID-19 crisis, proxied by GDP growth, on dividend policy. This study has implications for company management when considering investment opportunities that can moderate dividend policy during a crisis. Additionally, it advises investors to pay attention to the moderation of investment opportunities on the impact of the COVID-19 crisis on dividend policy to achieve optimal stock investment returns, especially dividend returns. The originality of this research lies in testing the moderation of investment opportunity on the impact of the COVID-19 crisis on dividend policy.